2017
DOI: 10.24099/vet.arhiv.160314
|View full text |Cite
|
Sign up to set email alerts
|

Establishing reference intervals for haematological and biochemical blood variables in Lika pramenka sheep

Abstract: Haematological and blood biochemical variables are key elements for routine assessment of animal health status, with implications in animal production and food safety. However, only reliable reference intervals of haematological and biochemical blood variables can provide the basis for accurate interpretation of the obtained blood results. Haematological and biochemical blood values critically dependent on living conditions, region, husbandry, rearing location, and diet. The aim of this study was to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
(36 reference statements)
4
7
0
1
Order By: Relevance
“…The average concentrations of hemogram and biochemical indicators in the blood of lambs remained normal at the beginning of the experiment, which is based on average values for RBC concentrations in sheep (8–13 (× 10 6 ) RBC/mL) [27]. The MCV values of the treatments were within the normal range of 23–48 fl [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average concentrations of hemogram and biochemical indicators in the blood of lambs remained normal at the beginning of the experiment, which is based on average values for RBC concentrations in sheep (8–13 (× 10 6 ) RBC/mL) [27]. The MCV values of the treatments were within the normal range of 23–48 fl [28].…”
Section: Discussionmentioning
confidence: 99%
“…The values of WBC, which can be used as an indicator of inflammation, were significantly different among groups. The mean concentration of WBC of the groups remained within the normal range (4000–12,000 × 10 9 /L) [27,28]. The absence of any effect on B Neuts and S Neuts indicated that the source of protein has no effect on the blood profile.…”
Section: Discussionmentioning
confidence: 99%
“…Shek Vugrovečki et al (2017) in the Lika Pramenka sheep determined normal distributions for RBC, HGB, MCV, MCH, UREA and TPROT and log normal or nonnormal distributions for other hematology and biochemistry parameters. Our results show that a large number of parameters in the tested rams do not show a normal distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Blood biochemical parameters were compared with the values obtained from geographically close regions as well as from the globally recognized literature. Shek Vugrovečki et al (2017) found the following benchmarks for blood biochemical parameters in Lika Pramenka sheep: TPROT 66.7-91 g/L; ALB 35.4-47.5 g/L; UREA 6-10.9 mmol/L; TBIL 5-11 μmol/L; GLU 1.4-3.7 mmol/L; CHOL 0.74-2.7 mmol/L; and AST 110-241 IU/L. Šimpraga et al (2013) reported the following reference values for the biochemical parameters: TPROT 66.8-87.4 g/L; ALB 28.5-44.7 g/L; UREA 3.5-7.8 mmol/L; GLU 2.9-4.3 mmol/L; AST 66.2-129.3 IU/L.…”
Section: Discussionmentioning
confidence: 99%
“…. Pre (A)-and post (B)-research blood sugar (BS), total protein (TP), triglycerides (TG), urea blood urea nitrogen (BUN) blood calcium (Ca), blood potassium (K), blood phosphorus (P), blood chlorine (Cl), blood sodium (Na) ( In the literature, the blood Na levels of lambs have been reported in the range of 142.38-154.09 mg dl -1 (Bórnez et al 2009; Al-dain and Jarjeis 2015) and have been reported to be affected by the Na level of the ration (Vugrovečki et al 2017). In the present study, Na levels of the lambs in the SHII group were slightly lower than those of the C and SHI group.…”
Section: (3): 2260-2269 2020mentioning
confidence: 99%